The Effect of Current Ratio on Return on Assets in Consumer Goods Companies Listed on the Indonesia Stock Exchange - U. Udayat; Martha Ayerza Esra; B. Brastoro (Manunggal Halim Jaya, 2026)
The consumer goods sector plays an important role in the Indonesian economy because it provides necessities with relatively fast cash turnover. In dynamic economic conditions, liquidity management can affect financial performance. This study aims to examine the effect of the Current Ratio (CR) on Return on Assets (ROA) in consumer goods companies listed on the Indonesia Stock Exchange (IDX). The study uses a quantitative, associative-causal approach. The population includes all consumer goods issuers on the IDX, with a purposive sample of 45 companies. Secondary data were obtained from annual financial reports for the 2018–2022 period on the IDX official website. The analysis uses simple linear regression. The results show that CR has a weak negative relationship with ROA, which is not statistically significant (p = 0.060), suggesting that higher liquidity is not always associated with higher profitability. The implications of these findings confirm that companies need to manage liquidity at an adequate level (not excessive) so that current assets do not become idle funds, while also increasing asset utilisation efficiency to optimise ROA.